Community members' evaluations of police-civilian interactions - Khogali, Mawia (Applied psychology in criminal justice, 2017)
We investigated the relationship between a suspect's race and participants' evaluations of police-civilian interactions. Participants were assigned to one of four role play conditions that manipulated a suspect's race (Black, White, or Latino): (1) as a police officer evaluating their own interaction with a suspect, (2) as a civilian evaluating their own interaction with a suspect, (3) as a police officer evaluating the interaction between another police officer and a suspect, and (4) as a civilian evaluating the interaction between another civilian and a suspect. Participants read a vignette and rated how resistant and disrespectful they found the suspect. Overall, White suspects were rated as more resistant than both Latino and Black suspects and more disrespectful than Black suspects. Moreover, participants evaluating their own interaction with the suspect rated the suspect as more resistant than participants evaluating the interaction of another person with the suspect. Finally, participants playing the role of a civilian rated the suspect as more resistant than participants playing the role of a police officer. We discuss the implications of these findings in the context of the current national concern about police-civilian relations.